Kalça Artroplastisi Uygulanan Hastada Gözlenen Pigmente Villonodüler Sinovit - Dabak, Nevzat; Çıraklı, Alper; Kandemir, Bedri; Göçer, Hasan (My University, 2014)
Pigmente villonodüler sinovit (PVNS) nadir görülen, benign ancak lokal agresif bir tümördür. Sinovial membranın proliferasyonu ile karakterizedir, ancak tendon kılıfları ve bursalarda da görülebilir. Klinik olarak soliter lezyonlar eklemde serbest cismi düşündüren sıkışma veya kilitlenme ile bunu takip eden efüzyon bulguları verir, diffüz lezyonlarda ise ağrı ve kronik şişlik mevcuttur. Yazımızda asetabulumda kistik lezyon nedeniyle takipli olan, kalça ekleminde ileri derecede osteoartrit ve buna bağlı ağrı şikayeti nedeniyle total kalça artroplastisi uygulanan, intraoperatif farkedilen ilginç PVNS olgusunu litelatür eşliğinde sunduk.

Pigmented villonodular synovitis (PVNS) is a rare, benign, but a locally aggressive tumor. It is characterized by the proliferation of synovial membrane, but it can also be seen in tendon sheaths and bursae. Clinical presentation of solitary lesions include compression and locking of the joint suggesting loose bodies in the joint and a subsequent findings of an effusion, whereas diffuse lesions manifest with pain and chronic swelling. In this article, we presented a curious case of PVNS in a female patient who have been followed up due to an acetabular cystic lesion. She underwent total hip arthroplasty for severe osteoarthritis of the hip joint and associated pain. The diagnosis of PVNS was established intraoperatively.
Pigmented Villonodular Synovitis in a Patient who Underwent Hip Arthroplasty
Keywords: Genel ve Dahili Tıp